Potential of Morage Leaf Combination of Rice Flour as A Mask for Healing Acne Vulgaris - Suwanto, -; Umah, Khoiroh; Zulmiatin, Silvia (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Tumour budding is defined as a small cluster of cancer cells (less than 5 cells) and isthe first step in invasion and metastasis. It has been best studied in colorectal carcinoma, where itis associated with a poor prognosis. Recently it has been studied in breast carcinoma, where it hasbeen shown to be associated with adverse clinico-pathological parameters. Objective: To assess thetumour budding in cases of infiltrating ductal carcinoma of breast, and to correlate its relation toP53 and Ki67 expression. Methods: This retrospective study was conducted from September 2022to September 2023. Tumor buds were assessed and graded into a three‑tier grading system. P-53and Ki-67 expression was graded based on percentage positivity of tumour cells. The correlationbetween tumour budding and p53 and Ki-67 expression was studied along with other clinicpathologicalparameters. Results: Grade 1 tumour budding was observed in 30% cases, Grade 2tumour budding was seen in 33.33 % and Grade 3 tumour budding were seen in majority of cases(36.67%,). There was a statistically significant correlation between tumour budding and increasedKi-67 expression (p=0.00065). P-53 expression and tumour budding showed no significantcorrelation (p=0.159). There was a significant association in relation to increasing histologic grade(p=0.0031) and presence of lympho-vascular invasion (p=0.044). Conclusion: Tumour budding isseen to associated with parameters favouring poor prognosis. Further studies with larger samplesize are needed to ascertain its role as an added prognostic marker. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 354-360